Ekstrak Etanol 96% Daun Mimba (Azadirachta indica Juss) Pada Malassezia Furfur - Ana Maria Ulfa; Indah Rizkiyah (Jurnal Ayurveda Medistra, 2026)
Malassezia furfur is a lipophilic fungus that is the primary causative agent of various skin disorders such aspityriasis versicolor (tinea versicolor) and seborrheic dermatitis. Long-term use of synthetic antifungals oftencauses side effects and the risk of resistance. Neem leaves are known to contain secondary metabolites withpotential as natural antimicrobials. The aim of this study was to identify compounds found in neem plants thatcan be used as antifungals. Emulgel preparations of 96% ethanol extract of neem leaves used threeformulations: 3%, 3.5%, and 4%. The research method used was an experimental method with descriptiveanalysis including organoleptic and statistical analysis including viscosity, pH, spreadability, andadhesiveness. The results showed that all three formulations had antifungal properties against Malasseziafurfur, with an average inhibition zone value of 0.58 mm for F1, 1.11 mm for F2, and 1.1 mm for F3. It can beconcluded that the neem leaf (Azadirachta indica juss) emulgel preparation has the highest antifungalproperties in formulation 2, with an inhibition zone diameter of 1.11 mm